An investigation on 10 graders’ anxiety at pre-stage in English writing lessons at Tien Thinh High School, Me Linh, Hanoi: Causes and Solutions - Trinh, Thu Huong (ĐHNN, 2017)
When teaching writing skill for 10th grade students at Tien Thinh High School, the author of this research realized that many students felt anxious in their writing lessons for several reasons. Pre-writing stage plays an important part in reducing students (...)